Aktivitas antidiabetes dan antioksidan pati jagung yang dikonjugasi dengan katekin [Antidiabetic and antioxidant activities of catechin conjugated corn starch] - Nurdin, Samsu Udayana; Salita, Siti Restia; Oktaviani, Celly; Subeki, Subeki; Herdiana, Novita (Jurnal Teknologi & Industri Hasil Pertanian, 2023)
High levels of carbohydrate consumption, especially starch, are considered to be an important risk factor for diabetes mellitus (DM). Conjugation of starch with phenolic compounds those have antidiabetic activity such as catechin is suggested increase health benefit of the starch.  Objective of this research was to find out optimal catechin concentration that was able to be conjugated into corn starch to produce conjugated starch with high antidiabetic and antioxidant properties. The synthesis of starch-catechin conjugates used free-radical grafting (FRG) by adding different concentration of catechin, namely 0%, 0,5%; 1%; 1,5%; and 2%. The result of the research indicates that increasing of catechin concentration grafted into starch increase the phenolic content of the starch. Conjugation of catechin into starch posed higher antidiabetic and antioxidant activities. Starch conjugated with 2.0% catechin had the best antidiabetic and antioxidant activities, therefore, it had potentiality to develop as functional starch for diabetes patients.